Christian political witness - Kalantzis, George (Downers Grove, Illinois : IVP Academic, An imprint of InterVarsity Press, 2014)
"My kingdom is not of this world." Followers of Jesus have been struggling to understand these words ever since he first uttered them -- often in sharply contradictory ways. Today the inescapably political nature of Christian witness is widely recognized. But what is the shape of this witness? What should Christian political engagement look like today? The twelve essays in this volume, originally presented at the 2013 Wheaton Theology Conference, present biblical, historical and theological proposals for thinking responsibly about the intersection of church and state in the contemporary cultural situation. Prophetic and pastoral, this book offers a fresh look at a crucial and contested dimension of the Christian life.
Church matters / Stanley Hauerwas -- The peril and potential of Scripture in Christian political witness / Mark A. Noll -- Extra ecclesiam nullum regnum: the politics of Jesus / Scot McKnight -- The political vision of the apostle to the nations / Timothy G. Gombis -- A witness to the nations : early Christianity and narratives of power / George Kalantzis -- Not so private : a political theology of church and family / Jana Marguerite Bennett -- Are corporations people? : the corporate form and the body of Christ / William T. Cavanaugh -- Violence / Peter J. Leithart -- Just war as Christian politics / Daniel M. Bell Jr. -- Repentance as political witness / Jennifer M. McBride -- Toward an evangelical social tradition : key current debates / David P. Gushee -- "You are in the world but not of it" / David Gitari.
Includes bibliographical references and indexes.
Keywords: Christianity and politics -- Congresses